PENGARUH LATIHAN DRILL TERHADAP KETEPATAN SMASH BULUTANGKIS ATLET PB. KIBER SAMBAS - Taufiq Febrisyah; Edi Purnomo; Rubiyatno Rubiyatno (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
ABSTRAK This study aims to determine the effect of drill practice on smash accuracy in athletes aged 11-12 years at PB.Kiber Sambas. This study uses an experimental method with the design of "One Group Pretest Posttest Design". The population in this study were PB. Kijang Berantai Sambas badminton athletes, totaling 12 athletes. The test instrument used for the initial measurement (pretest) and the final measurement (posttest) used a smash accuracy test. The results of the athlete's ability consisting of 12 samples obtained the pretest results for an average of 63.53, the lowest score was 50, the highest score was 72 with a standard deviation of 4.072 and the posttest results for an average of 66.2, the lowest score was 66, the highest score was 81 with standard deviation 5.055. Based on the results of the research data analysis, it can be stated that during the pretest, the score of smash ability was lower than the final test (posttest), so based on the results of the research and analysis of the influence test that has been done, it can be concluded that there is an effect of drill practice on smash accuracy. badminton athlete at PB Kiber Sambas.